IMPLEMENTASI DIAGNOSA KEBUTUHAN BELAJAR ANAK PADA PAUD INKLUSIF YANG BERKEADILAN DI TK ISLAM NURUL HUDA SAMARINDA - Syakiro, Imma; Nurul Qomariah; Zaidah; Indrawati A. Tajrin; Afrida Karim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Inclusive education at the early childhood education (PAUD) level requires an accurate and equitable diagnosis of learning needs as the basis for implementing learning. This study used a qualitative approach with a case study design and was analyzed using the SWOT approach. Data collection was conducted through observation, in-depth interviews, and documentation studies of inclusive PAUD principals and teachers. The results showed that the implementation of learning needs diagnosis has been carried out through observation and collaboration with parents, but has not been running optimally due to limited supporting facilities. On the other hand, government policy support and increased public awareness provide opportunities to strengthen the practice of learning needs diagnosis. This study concludes that strengthening teacher competency, developing adaptive diagnostic instruments, and multi-stakeholder collaboration can realize equitable and equitable inclusive education.